Imaging in detecting sites of pulmonary fibrosis induced by paraquat - Xu, Xiao-li (Second Affiliated Hospital of Zhejiang University School of Medicine, 2011)
BACKGROUND: The most common cause of death from paraquat (PQ) poisoning is respiratory failure from pulmonary fibrosis, which develops through pathological overproduction of extracellular matrix proteins such as collagens. In this study, a MicroCT system was used to observe dynamic changes of pulmonary fibrosis in rats with PQ poisoning, and find the characteristics of interstitial lung diseases via density-based and texture-based analysis of CT images of the lung structure. METHODS: A total of 15 male SD rats were randomly divided into a control group (n=5) and a PQ poisoning group (n=10). The rats in the poisoning group were intraperitoneally administered with 4 mg/ mL PQ at 14 mg/kg, and the rats in the control group were administered with the same volume of saline. The signs of pulmonary fibrosis observed by the MicroCT included ground-glass opacity, nodular pattern, subpleural interstitial thickening, consolidation honeycomb-like shadow of the lung. RESULTS: Compared with the control group, the rats with acute PQ poisoning had different signs of pulmonary fibrosis. Ground-glass opacity and consolidation of the lung appeared at the early phase of pulmonary fibrosis, and subpleural interstitial thickening and honeycomb-like shadow developed at the middle or later stage. MicroCT images showed that fibrotic lung tissues were denser than normal lungs, and their density was up-regulated with pulmonary fibrosis. There was no difference in the progress of pulmonary fibrosis between the right lung and the left lung (P>0.05), but there were differences in fibrosis degree at different sites in the lung (P<0.05 or P<0.01). Pulmonary fibrosis was mainly seen in the exterior area of the middle-lower part of the lung. CONCLUSION: Imaging can show the development of pulmonary fibrosis in PQ poisoning rats, and this method may help to administer drugs more reasonably in treating pulmonary fibrosis.